2013
DOI: 10.1113/expphysiol.2012.069443
|View full text |Cite
|
Sign up to set email alerts
|

Training‐induced acceleration of O2 uptake on‐kinetics precedes muscle mitochondrial biogenesis in humans

Abstract: New Findings r What is the central question of this study?A few weeks of endurance training accelerate the oxygen uptake (V O 2 ) on-kinetics in humans. The main aim of the present study was to determine whether the acceleration ofV O 2 onkinetics obtained by a short period of moderate-intensity training can be explained by an intensification of mitochondrial biogenesis. r What is the main finding and its importance?We demonstrated that 5 weeks of moderate-intensity training accelerates theV O 2 on-kinetics du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 53 publications
3
62
1
Order By: Relevance
“…In healthy skeletal muscle, faster V O 2 kinetics after endurance exercise training results primarily from improved oxidative capacity and/or allosteric regulation of mitochondrial respiration (i.e., 1"parallel activation"; Refs. 18,35,36,86,133,207,221,222,242,338,339) (see also Figs. 6 and 7).…”
Section: Muscle V O 2 (V Mo 2 )mentioning
confidence: 99%
“…In healthy skeletal muscle, faster V O 2 kinetics after endurance exercise training results primarily from improved oxidative capacity and/or allosteric regulation of mitochondrial respiration (i.e., 1"parallel activation"; Refs. 18,35,36,86,133,207,221,222,242,338,339) (see also Figs. 6 and 7).…”
Section: Muscle V O 2 (V Mo 2 )mentioning
confidence: 99%
“…These rapid increases in vasodilatory responses to exercise have been also demonstrated in humans (77). In support of the idea that endothelium-mediated mechanisms rather than adaptations requiring a longer time frame (such as increases in mitochondrial content or structural changes within the vasculature) were responsible for the improved matching of O 2 delivery to O 2 utilization observed in the aforementioned training studies (57,58), recent data from Zoladz and colleagues (89) have shown that a faster adjustment in the V O 2 kinetics response precedes changes in mitochondrial biogenesis and increases in capillarization.…”
Section: What Interventions Have Been Shown To Modify the V O 2 Kinetmentioning
confidence: 67%
“…These considerable improvements in measures of vascularization and endothelium-dependent vasodilation would improve the surface area for O 2 exchange, which might contribute to absence of an ''overshoot'' in the normalized [HHb]/V O 2 ratio in the trained older compared with the untrained older men. Nevertheless, despite the suggestion that improved O 2 provision to the active tissues plays a critical role in controlling the faster V O 2 kinetics observed in trained older individuals, mechanisms of intracellular control discussed in this review (34,35,40,41,68,88,89) are also to be acknowledged as ''limiting'' factors determining the rate of adjustment of oxidative phosphorylation.…”
Section: Can the Slower V O 2 Kinetics Typically Observed In Older Inmentioning
confidence: 72%
“…Notably, several training studies have provided some evidence indicating that regulation of muscle oxidative metabolism may be altered before any apparent changes in mitochondrial capacity (Green et al 2009, Layec et al 2013, Phillips et al 1995, Zoladz et al 2013). Phillips et al.…”
Section: Discussionmentioning
confidence: 99%
“…Some results suggest that HIT may not promote a coordinated increase in all enzymes involved in a metabolic pathway (Burgomaster et al 2006, MacDougall et al 1998), while others indicate that alterations in regulation of oxidative phosphorylation may precede changes in oxidative capacity (Green et al 2009, Layec et al 2013, Phillips et al 1995, Zoladz et al 2013), which raises a question about the influence of this type of exercise training on overall pathway fluxes in vivo . In particular, there is controversy regarding the effects of sprint training on ATP pathway flux during muscular activity (Burgomaster et al 2006, Green et al 2009, Harmer et al 2000, Jacobs et al 1987, Nevill et al 1989, Sharp et al 1986).…”
Section: Introductionmentioning
confidence: 99%